The Evidence on Globalization - Niklas Potrafke (Center for Economic Studies and ifo Institute (CESifo), 2014)
Globalization is blamed for many socio-economic shortcomings. I discuss the consequences of globalization by surveying the empirical globalization literature. My focus is on the KOF indices of globalization (Dreher 2006a and Dreher et al. 2008a), that have been used in more than 100 studies. Early studies using the KOF index reported correlations between globalization and several outcome variables. Studies published more recently identify causal effects. The evidence shows that globalization has spurred economic growth, promoted gender equality, and improved human rights. Moreover, globalization did not erode welfare state activities, did not have any significant effect on labor market interaction and hardly influenced market deregulation. It increased however within-country income inequality. The consequences of globalization thus turn out to be overall much more favorable than often conjectured in the public discourse.
Keywords: F00; F59; 330; globalization